AN EXPERIMENTAL STUDY ON THE USE OF SHORT ANIMATION STUDY IN ENHANCING STUDENTS’ VOCABULARY - Emes, Kezia; Maru, Gidion; Kukus, Fridolin (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
This research investigated the effectiveness of short animation videos in enhancing students’ English vocabulary at SMP Katolik Hati Kudus Manado. The study aimed to determine whether multimedia-based instruction could improve vocabulary mastery, retention, and motivation among junior high school students. A mixed-method approach was employed, combining quantitative and qualitative techniques. The quantitative phase used a pre-experimental design involving 23 eighth-grade students, while the qualitative phase included interviews with teachers and students. Data were analyzed using descriptive statistics, normality testing, and paired-sample t-tests with SPSS version 26, supported by thematic analysis for the qualitative data. The findings revealed a significant improvement in students’ vocabulary performance, with mean scores increasing from 35.07 in the pretest to 68.41 in the posttest (p < 0.001). The qualitative results indicated that short animation videos enhanced understanding, memory retention, and learning motivation through visual and auditory engagement. The study concluded that short animation videos effectively transformed vocabulary learning into an engaging and meaningful experience, leading to improved comprehension, confidence, and active participation. The research implies that multimedia learning can serve as an effective pedagogical tool for fostering cognitive and affective development in English language education.